Menanamkan Etos Kerja dan Jiwa Wirausaha melalui Pendidikan Agama Islam - Nafisatur Rosyidah; Monica Kusuma Maharani; Ahmad Syaifullah (Journal of Humanities, Social Sciences, and Education, 2025)
Islamic Religious Education (PAI) plays a strategic role in shaping students' character, including the work ethic and entrepreneurial spirit needed to face global socio-economic challenges. This literature study aims to analyze the concept of work ethic from an Islamic perspective, entrepreneurial values ​​within Islamic teachings, and how PAI can be an effective means of instilling these two aspects. The research method uses a qualitative approach with a literature review technique of books, national and international journals, and related educational documents. The results of the study indicate that the concept of work ethic in Islam is based on the values ​​of sincerity, responsibility, discipline, trustworthiness, and hard work (al-jiddiyyah). Meanwhile, Islamic entrepreneurial values ​​are reflected in the principles of honesty, creativity, professionalism, courage to take risks, and orientation towards the benefit of the community. PAI plays a role in instilling these values ​​through materials on morals, muamalah jurisprudence, teacher role models, habituation, and project-based extracurricular activities. The integration of PAI learning with entrepreneurial practice learning has also been proven to increase student motivation, creativity, and independence. In conclusion, Islamic Religious Education (PAI) is not only an instrument for spiritual strengthening, but also a means of developing human resources with a strong work ethic and entrepreneurial spirit. Therefore, curriculum innovation, contextual learning methods, and school-community collaboration are needed to strengthen PAI's role as a driver of productive character in the younger generation.